Mechanisms of Attachment of Neutrophils to Candida albicans Pseudohyphae in the Absence of Serum, and of Subsequent Damage to Pseudohyphae by Microbicidal Processes of Neutrophils In Vitro - Diamond, Richard D. (1978)
Mechanisms were studied that might explain the attachment and damage to Candida albicans pseudohyphae by neutrophils in the absence of serum. Attachment of neutrophils to pseudo hyphae was inhibited by Candida mannans (1-10 mg/ml), but not by mannose, dextran, chitin, conconavalin A, or highly charged polyamino acids. Contact was also inhibited by pretreatment of Candida before incubation with neutrophils with chymotrypsin, but not trypsin or several inhibitors of proteases. Similar results were obtained with pretreatment of neutrophils, except that trypsin was inhibitory. When pseudohyphae were killed with ultraviolet light, proteinpolysaccharide complexes of mol wt <10,000 were released which appeared to bind to the surfaces of neutrophils and inhibit contact between neutrophils and Candida, as well as other fungi. Damage to Candida by neutrophils was inhibited by agents known to act on neutrophil oxidative microbicidal mechanisms, including sodium cyanide, sodium azide, catalase, superoxide dismutase, and 1, 4 diazobicyclo (2, 2, 2) octane, a singlet oxygen quencher. Neutrophils from a patient with chronic granulomatous disease did not damage Candida at all. However, the hydroxyl radical scavengers mannitol and benzoate were not inhibitory. Cationic proteins and lactoferrin also did not appear to play a major role in this system. Low concentrations of lysozyme which did not damage Candida in isotonic buffer solutions damaged pseudohyphae in distilled water. Isolated neutrophil granules damaged pseudohyphae only with added hydrogen peroxide and halide, and damage occurred only with granule fractions known to contain myeloperoxidase. These findings suggest that neutrophils recognized a molecule on the Candida surface which has a chymotrypsin sensitive protein component, and which may be liberated from the cell surface upon death of organism. The neutrophil receptors for Candida appear to be sensitive to trypsin and chymotrypsin. Damage to Candida by neutrophils occurred primarily by oxidative mechanisms, including the production of superoxide and hydrogen peroxide interacting with myeloperoxidase and halide, as well as singlet oxygen, but did not appear to involve hydroxyl radical. Lysozyme might have an accessory role, under some conditions.